Directional resolution of dish antenna experiments to search for WISPy dark matter - Jaeckel, Joerg; Knirck, Stefan (Arxiv, 2015)
Dark matter consisting of very light and very weakly interacting particles such as axions, axion-like particles and hidden photons could be detected using reflective surfaces. On such reflectors some of the dark matter particles are converted into photons and, given a suitable geometry, concentrated on the detector. This technique offers sensitivity to the direction of the velocity of the dark matter particles. In this note we investigate how far spherical mirrors can concentrate the generated photons and what this implies for the resolution in directional detection as well as the sensitivity of discovery experiments not aiming for directional resolution. Finally we discuss an improved setup using a combination of a reflecting plane with focussing optics.